Soil fertility of peach orchards at installation and first year plant growth - Simões, M.P. (2020)
In Portugal the main peach (Prunus persica) production area is located in the central region of the country, where cherry and almond production coexist. This region is characterized by mild winters and dry hot summers. The annual rainfall ranges from 600 mm to 800 mm and the maximum temperature sometimes rises up the 40ºC. These climatic conditions are favorable to soil organic matter degradation. However, techniques of soil maintenance of no row mobilization and soil grass cover between rows used in peach orchards can have a positive effect on soil organic matter content as well as on soil fertility. In order to monitor the effect of orchard management on soil fertility we monitored 30 peach orchards in the Beira Interior region through an experimental unit/orchard, marked just after orchard installation. In each experimental unit soil samples were collected in planted row (1 m from the marked plant) and in the space between rows (2 m from the marked plant), to monitor both the effects of orchard management of row and between row space. All the sampling points were geo-referenced. After the first cycle, plant vigor was evaluated by Trunk Sectional Area (TSA) and correlated with soil fertility parameters and agricultural practices. The main results indicate that just after plantation organic matter content was 2.8% and there were no significant differences between row and between row samples. The average soil pH was 6.3 in row and 6.1 between rows. The average P2O5 content was 201 mg.kg-1 in row and 114 mg.kg-1 between rows. K2O content was 404 mg.kg-1 in row and 242 mg.kg-1 between rows. These results indicate that at plantation time, there was deep fertilization in the rows. Principal Component Analysis indicates that first year plant growth was negatively correlated to the presence of weeds during first annual cycle and to soil copper content.